Discovery of novel substituted octahydropyrrolo[3, 4-c]pyrroles as dual orexin receptor antagonists for insomnia treatment. Issue 6 (15th March 2017) - Wu, Songliang; Sun, Yu; Hu, Yi; Zhang, Hongmei; Hou, Lijuan; Liu, Xing; Li, Yufeng; He, Haiying; Luo, Zhi; Chen, Yuan; Wang, Yuhe; Shi, Weihua; et al.
Graphical abstract: Abstract: A series of octahydropyrrolo[3, 4- c ]pyrroles were synthesized and evaluated by orexin 1 and 2 receptor (OX1 & 2 R) antagonists assays. Compound14l with potent OXR antagonist activity and suitable pharmacokinetic behavior was chosen to be investigated in an EEG study, which demonstrated effects of sleep promotion comparable to Suvorexant. Furthermore, the di-fluro substituted analogs exhibited reduced hERG inhibition while maintaining moderate potency.